Sex chromosome contributions to sex differences in multiple sclerosis susceptibility and progression. (January 2018) - Voskuhl, Rhonda R; Sawalha, Amr H; Itoh, Yuichiro
Background: Why are women more susceptible to multiple sclerosis, but men have worse disability progression? Sex differences in disease may be due to sex hormones, sex chromosomes, or both. Objective: Determine whether differences in sex chromosomes can contribute to sex differences in multiple sclerosis using experimental autoimmune encephalomyelitis. Methods: Sex chromosome transgenic mice, which permit the study of sex chromosomes not confounded by differences in sex hormones, were used to examine an effect of sex chromosomes on autoimmunity and neurodegeneration, focusing on X chromosome genes. Results: T-lymphocyte DNA methylation studies of the X chromosome gene Foxp3 suggested that maternal versus paternal imprinting of X chromosome genes may underlie sex differences in autoimmunity. Bone marrow chimeras with the same immune system but different sex chromosomes in the central nervous system suggested that differential expression of the X chromosome gene Toll-like receptor 7 in neurons may contribute to sex differences in neurodegeneration. Conclusion: Mapping the transcriptome and methylome in T lymphocytes and neurons in females versus males could reveal mechanisms underlying sex differences in autoimmunity and neurodegeneration.